Urbanization and Elderly Welfare: Dynamic Evidence from Indonesia - I Made Jyotisa Adi Dwipatna; Shadry Andriani; Regina; Dirmansyah Darwin; Hafid Sumarwadji (Hasanuddin Economics and Business Review, 2026)
This study examines the relationship between urbanization and elderly welfare in Indonesia by integrating social, economic, and demographic dimensions, addressing the widely held assumption that urban development automatically enhances the well-being of older populations. Using balanced panel data from 34 Indonesian provinces for the period 2017–2022, obtained from the Indonesian Central Bureau of Statistics and the Ministry of Health, the study employs a dynamic panel model estimated through the Generalized Method of Moments (GMM) to capture short- and long-term effects while accounting for endogeneity. The results indicate that past elderly welfare conditions do not significantly influence current welfare levels. Urbanization is found to have no statistically significant effect on elderly welfare in either the short or long term. In the short term, health facility availability, poverty levels, and the proportion of elderly individuals negatively affect elderly welfare, whereas economic well-being exerts a positive influence. In the long term, economic well-being remains a key positive determinant, while the proportion of elderly individuals continues to have a negative effect. Overall, the findings demonstrate that elderly welfare in Indonesia is shaped primarily by socioeconomic factors rather than by the pace of urbanization. The study contributes original policy-relevant insights by challenging urbanization-centered development strategies and emphasizing the importance of targeted economic empowerment and inclusive social protection systems to improve elderly welfare.